Biological markers of Alzheimer?s disease - Leonardo Cruz de Souza; Marie Sarazin; Antônio Lúcio Teixeira Júnior; Paulo Caramelli; Antônio Emanuel dos Santos; Bruno Dubois (Arquivos de Neuro-Psiquiatria)
The challenges for establishing an early diagnosis of Alzheimer’s disease (AD) have created a need for biomarkers that reflect the core pathology of the disease. The cerebrospinal fluid (CSF) levels of total Tau (T-tau), phosphorylated Tau (P-Tau) and beta-amyloid peptide (Aβ42) reflect, respectively, neurofibrillary tangle and amyloid pathologies and are considered as surrogate markers of AD pathophysiology. The combination of low Aβ42 and high levels of T-tau and P-Tau can accurately identify patients with AD at early stages, even before the development of dementia. The combined analysis of the CSF biomarkers is also helpful for the differential diagnosis between AD and other degenerative dementias. The development of these CSF biomarkers has evolved to a novel diagnostic definition of the disease. The identification of a specific clinical phenotype combined with the in vivo evidence of pathophysiological markers offers the possibility to make a diagnosis of AD before the dementia stage with high specificity.